Exploring the heterogeneity of HER2 gene status and expression in non-positive breast cancer patients: insights from immunohistochemistry and fluorescence in situ hybridization - Jingmin Zhong; Beibei Gao; Qingjie Wang; Jun He; Danjv Luo; Chen Zhang; Jun Fan; Xiu Nie (Diagnostic Pathology)
Abstract Breast cancer became the most prevalent malignancy among women, and HER2 expression status is critical for treatment decisions. With the emergence of ADC drugs, HER2 low-expressing patients who previously did not respond well to traditional anti-HER2 therapies may now benefit. In this study, immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH) were applied to assess HER2 expression in 349 patients with HER2-non-positive breast cancer. Our analysis revealed that HER2-low tumors exhibited fewer grade III tumors (39.74% and 55.65%, respectively, P = 0.005) and higher positivity for estrogen receptor (ER, 88.89% vs. 61.74%, P < 0.001) and progesterone receptor (PR, 84.62% vs. 57.39%, P < 0.001) compared to HER2-ZERO tumors. Of the 349 cases, IHC was ultimately evaluated in 327, the antibodies demonstrated only 64.22% (95% CI: 58.76–69.42%) agreement between clone 4B5 and clone EP3. Pathologist 1, who had more extensive working experience, demonstrated higher consistency (94.19%) with the gold standard when using clone EP3, compared to Pathologist 2 (74.31%). FISH analysis revealed significant differences in HER2/CEP17 ratio and average HER2 copy numbers between HER2-ZERO and HER2-low tumors, but no clear cut-off value could be identified. Notably, HER2/CEP17 ratio mostly between 1 and 2, with HER2-ZERO tumors primarily ≤ 1.4, and average HER2 copy numbers were mostly ≥ 2 and < 4, with HER2-ZERO tumors primarily ≤ 2.5. Despite distinct clinicopathological features, FISH remains inadequate for distinguishing HER2-low from HER2-ZERO expression. Further studies are needed to improve HER2 assessment in this challenging subset of patients.